An investigation of friction-based tendon sheath model appropriate for control purposes - Tjahjowidodo, Tegoeh (2013)
The tendon sheath mechanism plays an important role in many robotic systems from surgical devices to robot hands. However, many unexpected properties such as nonlinear hysteresis and backlash, which appear in the tendon sheath system, cause major losses in force transmission. This report deals with the characterization of hysteresis phenomenon, which is attributed to the presence of frictional effects on its elements, in a tendon-sheath driven surgical robot. Unlike various approaches presented in the literature that utilized multiple lumped mass elements, this proposed approach models the tendon sheath as one element. A new dynamic friction model that allows accurate description of friction lag and hysteresis behavior in two regimes, i.e. presliding and sliding regimes, for a sheath in arbitrary configuration such as helical and spatial shape has been developed.